Overcoming strategic persistence: Effects of multiple scenario analysis on strategic reorientation - Healey, Mark P.; Hodgkinson, Gerard P. (Strategic management journal, 2024)
Research Summary To thrive in an unpredictable world, managers must adapt their decision‐making to changing events. However, a major impediment to adaptation is strategic persistence, that is, the tendency to stick with previously successful strategies. We examined whether multiple scenario analysis can help to overcome the dysfunctional effects of strategic persistence. In a laboratory study using a multi‐round strategy simulation that required players to change strategies to succeed, we found that multiple scenario analysis alleviated the effects of strategic persistence by stimulating strategic reorientation, that is, adaptive shifts in patterns of strategic choice. Multiple scenario analysis influenced strategic reorientation indirectly, by fostering belief in a new strategy, and its effectiveness depended on prior performance. We discuss implications for research on the cognitive microfoundations of strategic adaptation. Managerial Summary What can managers do when their previously successful strategy stops working? We found that using multiple scenario analysis, a common strategic planning technique can help decision makers switch to a new strategy. In our study, using a business simulation game that required players to change strategies to succeed, we found that those players who imagined different industry futures as part of a multiple scenario analysis exercise were more likely to believe in new strategies and as a result more likely to switch to the winning strategy. However, this intervention was less effective for players who had high levels of success with the old strategy. We discuss how scenario‐based intervention techniques can be used to assist managers with reorientating to a new strategy.